Efficacy and safety of dynamic neuromuscular stabilisation in treating chronic non-specific low back pain: a systematic review and meta-analysis protocol - Bin Huang; Linlin Zhang; Yu Pu; Xiaoming Xi; Hongyan Bi; Shifang Cui (BMJ Open)
Introduction Chronic non-specific low back pain (CNLBP) stands as a predominant factor contributing to disability worldwide. In the recent past, the sphere of medical research has witnessed a burgeoning interest in exploring the therapeutic potential of dynamic neuromuscular stabilisation (DNS) techniques for this condition. Despite the growing body of evidence, a comprehensive synthesis evaluating the effectiveness and safety of these interventions remains absent. This study, therefore, seeks to rigorously assess the therapeutic value and safety profile of DNS techniques in the management of CNLBP.Methods and analysis We will explicitly follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for conducting the systematic review. Our search strategy will encompass both English and Chinese databases, extending from their inception through March 2024. Specifically, we will explore the Web of Science, PubMed, Embase and the Cochrane Library for English literature, while for Chinese studies, we will delve into the Chinese National Knowledge Infrastructure, the Chinese Science and Technology Periodical Database (VIP), the Wan Fang Database and the China Biology Medicine disc. The outcome metrics we will assess include clinical efficacy, pain (assessed using the Visual Analogue Scale (VAS) and Numerical Pain Rating Scale (NPRS)) and functional disability (evaluated using the Oswestry Disability Index (ODI) and Roland-Morris Disability Questionnaire (RMDQ)) and the incidence of adverse reactions. Our focus will be on identifying randomised controlled trials that assess the efficacy of DNS training in the treatment of CNLBP. The data extracted from these trials will be synthesised through a comprehensive meta-analysis to elucidate the effectiveness of this intervention. When applying the Grading of Recommendations Assessment, Development and Evaluation framework to assess the included studies, we may encounter several challenges, for example, the variability in outcome measurements, the sample sizes of the included studies and the heterogeneity of the study populations. We will pay particular attention to these potential limitations to ensure the accuracy and reliability of the evaluation.Ethical considerations and dissemination Given that our research does not engage human or animal subjects nor does it handle any personal patient data, the requirement for ethical approval is bypassed. We aim to share the insights gleaned from this study through publication in reputable peer-reviewed journals and presentation at professional conferences, ensuring broad and impactful dissemination of our findings.